Hubungan antara Motivasi Kerja dengan Kinerja Karyawan - Octavianasari, Putri; Dwityanto O. S.Psi, M.Si, Achmad Dwityanto O. S.Psi, M.Si (2017)
The organization usually believe that to achieve the objectives of the Organization should pay attention to the performance. Employee performance becomes very important due to the decline in the performance of either individuals or groups within an enterprise can provide a meaningful impact in an enterprise, that will have an impact on the achievement of business objectives of the organization.One of the factors of employee performance is work motivation. The aim of this research is to know is the relationship between work motivation with employee performance. The hypothesis proposed that there are positive relationship between work motivation with employee performance. Technique the sample used ini this research was using a technique purposive sampling there are 56 respondents. This research used quantitative methods with work motivation scale and methods of documentation employee performance as a measurement. Data analysis on this research using SPSS 17.0 with product-moment correlation method, obtained 0,459 of correlation and 0,000 (p≤0,01) of significant (p) which showed that there is a positive relationship between work motivation with employee performance. Work motivation relatively high with empirical average (EA) = 161, 75 and hypothetical average (HA)=125. Employee performance relatively good with empirical average (EA)=35,41 and hypothetical average (HA)=30. Effective contribution from two variables showed by determinant coefficients (r^2)= 0,211 it means work motivation affects by 21,1% to employee performance and there is 78,9% is influenced by other factors. As for aspect of work motivation variable that has the most dominant influence toward employee performance is responsibility to work with effective contribution shown 0,440 or 19,4%.